Potencial genético e químico dos endófitos de Murraya paniculata L. (Jack) - Souza, Antonia Queiroz Lima de (2007)
The plant Murraya paniculata is native in Asia where its root barks have produced the contraceptive and hormonal alkaloid yuehchukene. In Brazilian specimens no alkaloid was detected. This had inspired new researches about the microorganisms that interact with it in Brazil, including the present work. Therefore, 1711 endophytic microorganisms were isolated from four host plants, in São Paulo State, and the seasonal colonization indexes, the microbial frequencies and the specificities of the identified groups per tissues (microhabitats) were verified. Among the obtained endophytes, 1061 were filamentous fungi and 650 were bacteria, with 62% and 38% of frequency and 33% and 20% of colonization index, respectively. The colonization indexes of the bacteria in comparison to the of fungi were lower in all gatherings and hosts, principally for leaves that, had shown the bigger frequency for the fungi and the smaller for the bacteria. Fungi were clustered in 20 morphological groups, 15 identified to genus level and five unknown, including two Mycelia sterilia. The recognized genera were Fusarium, Colletotrichum and its teleomorphs Giberella and Glomerella respectively, Trichoderma, Phomopsis, Paecilomyces, Penicillium, Aspergillus, Epicoccum, Pestalotiopsis, Alternaria, Xylaria, Nigrospora and Guignardia and the unknown were named A-E groups. The more frequent genera were rich in diversity, according to morphological and molecular data. A more diversity of fungi genera were verified in the winter (17) and a less in the spring (9) as the endophytic fungi were smaller in quantity in the summer (44.7%) and greater in the autumn (77.7%). From a sample of 59 isolates and six fungi as prototypes genomic DNAs were obtained and their ITS-1 regions were sequenced. The unknown strain B (Fed) had sequenced its 5.8s and ITS-2 regions. 21 species were identified by their ITS-1 regions and two others were hypothesized as novelty: one Trichoderma and the Fed that all morphological and chemotaxonomic studies appoint as a new species. Trichoderma associated to M. paniculata were in majority from barks and had showed great diversity of species (9). It was evaluated too the potential of the endophytes from host for bioactive metabolite production. The more promising groups for extracellular substances were the fungi Penicillium, with bactericidal and antiprotozoal actions, Pestalotiopsis, active against Candida, and Trichoderma, with fungicidal and bactericidal activities. For Fed it was noted its intracellular metabolites as strong bactericidal and its volatiles as anti-fungi. By looking for the active principles of those microorganisms, from Penicillium citrinum the citrinin and an undetermined alkaloid were obtained and from Trichoderma koningii 13 metabolites, including four koninginins related to those biological activities observed were identified. From Fed-3, 10 substances were obtained, seven fixed and three volatile, including a novel manosil guaiane type sesquiterpene and the new, as natural substances, 3-Hydroxy-5-phenylmethyl- (3S,5R)-b10-O-tetrahydrofuran-2-one and chloroacetonitrile. The chloroacetonitrile was suggested as the active principle of the Fed s volatiles. This work was important to reveal the diversity of the endophytes from Brasilian M. paniculata, the high variability of their more frequent genera, two possible novel species and the potential of them to produce bioactive and new metabolites. This work is hoped to contribute for understanding the endophytic microorganism biodiversity as well as their chemical and biotechnological potential.